STUDI MINERAL ALTERASI HIDROTERMAL LAPANGAN PANAS BUMI DIENG STUDI KASUS SUMUR, HCE-30, HCE-30A, HCE-31DAN HCE-28A - Candraditya, Lantip
Dieng Geothermal Field is geographically located at coordinates 7 ° 11'00 "LS - 7 ° 14'00" latitude and 109 ° 51'00 "E - 109 ° 54'30" longitude, and administratively located in Wonosobo Regency, Banjarnegara Regency and Pekalongan Regency, Central Java. The object of research is borehole cutting and fluid content of the well HCE-30 HCE -30A, HCE-31 and HCE-28A. The Dieng Geothermal Field is a mature field with indications of clay-cap formation, and has a high-temperature reservoir fluid (± 300°C), which has been produced by PT. Geodipa Energi. The problem formulation in this research is to find out the process that can change the condition of the reservoir’s fluid, the occurrence of hydrothermal alteration. This study shows that hydrothermal fluid has been on water-rock interaction proces and boiling proses at temperature 250-340°C. These processes causes the hydrothermal minerals alteration and change the fluid’s composition involve the increased of ratio unsure Ca/H, Na/H and K/H and the increase of reservoir fluid pH.